ILMU MUKHTALIF AL-HADIS - Nurul Hakim (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2017)
Hadith is positioned as a source of Islamic law after the Qur'an. Therefore, every Muslim should understand the hadith well. However, attempts to understand hadith are very difficult. Moreover, hadith that are contradict with other hadith. To understand hadith which is considered contradict to other hadith, the scholars make a discipline called mukhtalif al-h}adi>s |. This science is understood as: 1) there is a contradiction that involves two hadiths that are equal (s}ah}i>h}) or with the Qur'an, mind, history, or science and science of knowledge, 2) outward contradiction, 3) the contradiction was solved by using a certain method. With regard to epistemology, there are two sources used in the science of mukhtalif al-h}adi>s |, asba>b al-wuru>d and ijtiha>di>. In addition, there are five methods of dispelling the contradiction of a hadith namely, al-jam' wa al-taufi>q, al-tarji>h}, na>sikh-mansu>kh, tawaqquf, and takwil. And in determining the truth of science, correspondence theory is used in hadiths that use asba>b al-wuru>d as the source and theory of coherence used in hadiths that make ijtiha>di> (science) as the source.